THE DEVELOPMENT OF MATHEMATICAL MODELS OF THE DYNAMICS OF TRAINS IN THE WRITINGS OF YVES. A. LAZARYAN AND HIS DISCIPLES - Ye. P. Blokhin; L. A. Manashki (Nauka ta progres transportu, 2009)
The review of mathematical models of train dynamics.